Ultrafast-Laser-Induced Tailoring of Crystal-in-Glass Waveguides by Precision Partial Remelting - Alexey S. Lipatiev; Sergey V. Lotarev; Tatiana O. Lipateva; Sergey S. Fedotov; Elena V. Lopatina; Vladimir N. Sigaev (Micromachines, 2023)
Space-selective laser-induced crystallization of glass enables direct femtosecond laser writing of crystal-in-glass channel waveguides having nearly single-crystal structure and consisting of functional phases with favorable nonlinear optical or electrooptical properties. They are regarded as promising components for novel integrated optical circuits. However, femtosecond-laser-written continuous crystalline tracks typically have an asymmetric and strongly elongated cross-section, which causes a multimode character of light guiding and substantial coupling losses. Here, we investigated the conditions of partial remelting of laser-written LaBGeO5 crystalline tracks in lanthanum borogermanate glass by the same femtosecond laser beam which had been used for their writing. Exposure to femtosecond laser pulses at 200 kHz repetition rate provided cumulative heating of the sample in the vicinity of the beam waist sufficient to provide space-selective melting of crystalline LaBGeO5. To form a smoother temperature field, the beam waist was moved along the helical or flat sinusoidal path along the track. The sinusoidal path was shown to be favorable for tailoring the improved cross-section of the crystalline lines by partial remelting. At optimized laser processing parameters, most of the track was vitrified, and the residual part of the crystalline cross-section had an aspect ratio of about 1:1. Thermal-induced stress emerging during the tailoring procedure was efficiently eliminated by fine post-annealing. The proposed technique suggests a new way to control the morphology of laser-written crystal-in-glass waveguides by tailoring their cross-section, which is expected to improve the mode structure of the guided light.